Prediction of The Biogas Production and Electricity Generation from Food Waste Using Artificial Neural Network (ANN) for the Residential Area - Ahmad Jailani, Nur Shahirah; Jumaat, Siti Amely; Zainun, Noor Yasmin (Evolution in Electrical and Electronic Engineering, 2022)
Biogas is made through the anaerobic digestion of organic substrates, and it is the end product of microbiological fermentation, containing 60 percent methane and 40 percent carbon dioxide, respectively. The main objective of this research is to identify the potential of food waste to produce power generation by converting food waste into biogas. The aim of this project is to compare the calculation value and prediction value of the biogas production and electricity generation using the Artificial Neural Network (ANN) method. The food waste data for two residential areas in Parit Raja, Johor and Sri Gading, Johor was collected from Solid Waste Management (SWM) Sdn. Bhd., Batu Pahat, Johor from February 2021 until August 2021. The findings result for seven months of biogas production and electricity production by using ANN software and by calculation have been analysed and discussed accurately. The result shows that Taman Pura Kencana, Sri Gading, Batu Pahat, Johor shows the highest total biogas production which is 90.06 m³/month in April 2021 and followed by August 2021 with 50.77 m³/month. As a result, the electricity production was also high during these two months which is 1840.95 MWh in April 2021 and 1037.94 MWh in August 2021. It can be concluded that biogas production and electricity production can be predicted by using the Artificial Neural Network (ANN) software.